A NEW APPROACH TO ESTIMATION OF THE ECOLOGICAL PLASTICITY OF PLANT VARIETIES - W. G. Potanin; A. F. Aleinikov; P. I. Stepochkin (Вавиловский журнал генетики и селекции)
Problems of the improvement of estimation of the environmental plasticity of varieties and lines are considered. It is recommended to apply the proposed variety stability index. A final version of the analytical expression of the index for practical application is presented, as well as its typical values for Siberia.